Novel spoof surface plasmon polaritons on a planar metallic strip with periodic semi-elliptical grooves at microwave frequency. Issue 2 (22nd January 2019) - Anwar, Rana Sadaf; Wei, Yuan; Mao, Lingfeng; Li, Xijun; Ning, Huansheng
ABSTRACT: It is well known that traditional microstrip (MS) transmission lines suffer from high transmission losses at microwave and millimeter wave frequencies. To solve the issue, a novel periodic subwavelength structure is proposed in this work with semi-elliptical grooves (SEGs) on a lateral edge of MS line, for the propagation of spoof surface plasmon polaritons (SSPPs) in the microwave regime. Dispersion relations are analyzed by a numerical method using ANSYS's HFSS (High-Frequency Structure Simulator), and ability to operate efficiently in primary mode is demonstrated. A comparison with other structures is also accomplished and found that more strong resonant modes are created by the coupling between upper metal strip with textured SEGs and the lower ground layer which are confined near the surface of this grating structure. It has been observed that the cutoff frequency ( f c ) and the level of field confinement depend on the geometric parameters, and SEG-based SSPPs efficiently minimize the asymptotic frequency by 65% and 12% as compared to MS and Vee-groove structures, respectively. We further investigate a planar and highly efficient, low-pass plasmonic filter with 3 dB cutoff frequency of 11.4 GHz and significantly reduced insertion loss (>−1.9 dB) in the passband. A prototype is fabricated for validation by standard PCB manufacturing process; good agreement between experimental and simulation results confirms the excellent performance of this compact filter in the entire passband with smaller transmission losses. Such a plasmonic metamaterial structure presents a unique and highly unexplored geometry which strongly supports confined SSPPs, therefore, can play a significant role in advanced integrated plasmonics circuitry and applications.